(untitled) (Constructionism Conference Proceedings, 2025)
This paper investigates an Erasmus+ project entitled Children as Creators of Augmented Reality Stories (CARS), focusing on how children aged 10–12 create augmented reality stories for language learning, grounded in constructionist principles. We apply a SWOT analysis from teacher perspectives to highlight strengths, weaknesses, opportunities, and threats. The literature review underscores the gap in child-driven augmented reality narrative creation, linking it to collaborative, hands-on learning processes. The proposed research design outlines iterative methods for capturing students’ experiences, language gains, and the practical demands of augmented reality implementation. Results aim to inform educators on best practices, emphasizing resource availability, assessment frameworks, and sustainability considerations. By offering a constructionist lens, the study addresses both theoretical and applied implications, contributing to the broader discourse on augmented reality-based educational innovation while ensuring practical feasibility in diverse contexts.